Short-Term Safety of Booster Immunization With BNT162b2 mRNA COVID-19 Vaccine in Healthcare Workers. (31st December 2021) - Paran, Yael; Saiag, Esther; Spitzer, Avishay; Angel, Yoel; Yakubovsky, Michal; Padova, Hagit; Ben-Ami, Ronen; Goldinger, Ilana; Gamzu, Ronni; Sprecher, Eli; Zeltser, David; Henig, Oryan
Abstract: This study demonstrated a favorable short-term safety profile after a third dose of the BNT162b2 vaccine among healthcare workers (HCWs). There were more frequent local reactions and less systemic reactions compared to the second dose. The HCWs who reported reactions had higher prebooster titer of anti-S1 antibodies compared to those who reported no reactions.